Association between sleep disturbance and mental health of healthcare workers: A systematic review and meta-analysis - Liu, Ying; Zhang, Qin; Jiang, Fugui; Zhong, Hua; Huang, Lei; Zhang, Yang; Chen, Hong (Frontiers in Psychiatry, 2022)
Objectives: Sleep disturbance and mental health are challenges for healthcare workers (HCWs). Especially during the COVID-19 pandemic, they experienced more severe sleep and mental health problems. However, the association between sleep disturbance and the mental health of HCWs is still controversial. This study aimed to systematically review the relationship by conducting a systematic review and meta-analysis. Method: Two researchers retrieved the literature from Web of Science, PubMed, EMBASE, CINAHL, Psyclnfo, and Cochrane Library from the establishment of the databases until November 20, 2021. We used the New Castle-Ottawa Scale (NOS) and Agency for Healthcare Research and Quality (AHRQ) to evaluate the risk of bias in prospective research and cross-sectional research, respectively. The major exposure was HCWs’ sleep disturbance, and the major outcome was mental health. The correlation coefficients (r), regression coefficients (β) and odds ratios (OR) of the included studies were integrated. Result: Fifty-nine studies were included for qualitative analysis, of which 30 studies could be combined and entered into quantitative analysis. There were 23 studies during the COVID-19 pandemic among the 59 included studies. The results of the meta-analysis showed that the correlation coefficient between sleep disturbance and mental health was 0.43 (95% CI: 0.39-0.47). HCWs with sleep disturbance had a 3.74 (95% CI: 2.76-5.07) times higher risk of mental health problems than those without sleep disturbance. The correlation coefficient during the COVID-19 epidemic was 0.45 (95% CI: 0.37-0.53), while it was 0.40 (95% CI: 0.36-0.44) during the nonepidemic period. Subgroup analysis compared the OR results in epidemic and nonepidemic periods of COVID-19, which were 4.48 (95% CI: 2.75-5.07) and 3.74 (95% CI: 2.74-7.32), respectively. Conclusion: Sleep disturbance and mental health problems were positively correlated among HCWs. Particularly in the COVID-19 pandemic, more attention should be given to this issue.